An examination of Black women's experiences in undergraduate engineering on a primarily white campus: Considering institutional strategies for change. Issue 1 (18th December 2019) - Blosser, Emily
Abstract: Background: Black women are underrepresented in engineering and face barriers as a result of their race and gender. While existing research often focuses on strategies Black women can adopt to become successful engineers, this study asks how engineering institutions might change to better accommodate Black women. Purpose: The specific purpose of this study is to explore the following questions: (a) How does the educational environment in engineering marginalize Black women in ways that are beyond their control? (b) How can institutions transform their policies and practices to improve Black women's experiences and participation in engineering? Design/Method: I conducted interviews with 12 Black women studying engineering at one university. Informed by critical race theory and sociological theories of race, a constructivist grounded theoretical approach was used to identify and refine common themes across interviews. Results: The findings explore the ways Black women describe their marginalization. Common themes include an acute sense of isolation, grappling with hypervisibility, difficulties forming study groups, and regular exposure to microaggressions. Conclusions: By drawing attention directly to Black women's stories and experiences, this study offers ways to begin thinking about how institutions can adopt policies to recruit and retain more Black women in engineering. Strategies discussed include promoting new messages of inclusivity in engineering, supporting and creating "counterspaces, " and encouraging engineering educators to create student study groups and recognize microaggressions.